A flexible segment modified COF-5 composite polymer solid electrolyte and its preparation method and application
By modifying the COF-5 composite polymer solid electrolyte through flexible segments, the problems of low ion conductivity and insufficient mechanical strength caused by high crystallinity of the polymer matrix are solved, efficient ion transmission and battery stability are achieved, and the performance of solid lithium-ion batteries is significantly improved.
Patent Information
- Application Number
- CN202410837514.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-26
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-06-26
AI Technical Summary
The high crystallinity of existing polymer matrix results in poor ion migration, resulting in low ion conductivity, and insufficient mechanical strength to inhibit the growth of lithium dendrites, resulting in reduced capacity and short circuits within the battery.
Flexible segments are used to modify the solid electrolyte of COF-5 composite polymer. The coordinate reaction of the terminal amino-modified polyethylene glycol and COF-5 is carried out to form MCOF-5 particles, and it is combined with polyethylene oxide and lithium salt to improve the compatibility of COF-5 and polyethylene oxide, and achieve uniform dispersion and flexible modification of COF-5.
It significantly improves the Coulomb efficiency and cycle life of solid-state lithium-ion batteries, improves ionic conductivity and electrochemical properties, reduces the growth of lithium dendrites, and enhances the stability of the battery.
Smart Images

Figure CN118825390B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid electrolyte, in particular to a flexible segment modified COF-5 composite polymer solid electrolyte, and also to a preparation method and application of the solid electrolyte in a solid lithium ion battery, belonging to the technical field of lithium ion batteries. Background Art
[0002] The growing demand for high energy density storage systems in electric vehicles, portable electronic devices and other applications has prompted people to conduct in-depth and systematic research on secondary batteries to meet practical needs. Safety issues caused by leakage and combustion of liquid electrolytes commonly used in lithium-ion batteries are common. Therefore, it is of great significance to develop solid-state lithium-ion batteries with high safety, high energy density and wide temperature range.
[0003] Polymer solid electrolytes (SPEs) are considered to be the most promising new electrolytes due to their high flexibility, low cost, strong plasticity, and excellent interfacial compatibility with metallic lithium. However, the high crystallinity of the polymer matrix leads to poor ion migration and low ion conductivity, which is the biggest challenge facing this electrolyte. In addition, the mechanical strength of polymer electrolytes is not sufficient to inhibit the growth of lithium dendrites, which usually leads to reduced capacity and, more seriously, internal short circuits in the battery.
[0004] Therefore, it is of great significance to develop a solid polymer electrolyte with high conductivity and stable performance. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the first object of the present invention is to provide a flexible segment modified COF-5 composite polymer solid electrolyte, which has the characteristics of high ionic conductivity and good stability, and can improve the coulombic efficiency and cycle life of solid-state lithium-ion batteries.
[0006] The second object of the present invention is to provide a method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte, which is simple, has readily available raw materials, is low in cost, and is suitable for industrial-scale production.
[0007] The third object of the present invention is to provide an application of a flexible segment modified COF-5 composite polymer solid electrolyte, which has high ionic conductivity and stability and is used in solid-state lithium-ion batteries to significantly improve the coulombic efficiency and cycle life of the battery.
[0008] In order to achieve the above technical objectives, the present invention provides a flexible segment modified COF-5 composite polymer solid electrolyte, which comprises the following components: MCOF-5, polyethylene oxide and lithium salt; the MCOF-5 is obtained by coordination between terminal amino group modified polyethylene glycol and COF-5.
[0009] The flexible segment modified COF-5 composite polymer solid electrolyte of the present invention has a stable structure. The existing COF-5 material has a one-dimensional channel for rapid ion transmission. However, if the COF-5 material is directly added to polyethylene oxide to prepare a polymer electrolyte, the COF-5 material is prone to uneven dispersion and agglomeration. The present invention uses terminal amino-modified polyethylene glycol to modify COF-5. The terminal amino-modified polyethylene glycol coordinates with the COF-5 material to form MCOF-5 particles. Further adding it to the polymer solid electrolyte can effectively improve the compatibility of COF-5 and polyethylene oxide, and can achieve uniform dispersion of the COF-5 material and avoid its agglomeration. At the same time, the polyethylene glycol with an alkoxy ether chain forms a stable bond by coordination reaction with the boron atom in COF-5 through its terminal modified amino group, thereby realizing flexible modification of COF-5 and significantly improving its electrochemical properties when used as a polymer solid electrolyte filler; on the one hand, it utilizes the ether oxygen atoms in the alkoxy ether chain to effectively coordinate with lithium ions, and through the continuous breaking / forming process of lithium-oxygen bonds, the lithium ion transmission in the electrolyte is carried out through intra-chain or inter-chain hoops, which is beneficial to improving the transmission efficiency of lithium ions; on the other hand, surface modification of COF-5 with flexible polyethylene glycol can reduce the crystallization performance of COF-5.
[0010] As a preferred solution, the number average molecular weight Mn of the amino-terminated polyethylene glycol is 400-800 mol / g.
[0011] As a preferred solution, the mass ratio of COF-5 to the terminal amino-modified polyethylene glycol in the MCOF-5 is 1:1 to 2. If the ratio of the terminal amino-modified polyethylene glycol is too low, the modification effect cannot be achieved, and if the ratio of the terminal amino-modified polyethylene glycol is too high, too many flexible molecules will gather on the surface of the COF-5 material, resulting in a heterogeneous state of the material.
[0012] As a preferred solution, the mass ratio of MCOF-5 to polyethylene oxide is 3 to 9:100. The mass ratio of MCOF-5 to polyethylene oxide should not be too high or too low. If the ratio of MCOF-5 is too high, too many MCOF-5 particles will hinder the transmission of lithium ions to a certain extent, thereby reducing the ionic conductivity; if the ratio of MCOF-5 is too low, it will lead to no obvious improvement in performance. The mass ratio of MCOF-5 to polyethylene oxide is further preferably 3 to 7:100.
[0013] As a preferred solution, the ratio of the lithium salt to the polyethylene oxide is 1:15 to 20, with the molar ratio of the lithium ions in the lithium salt to the oxygen atoms in the polyethylene oxide being 1. The ratio of the lithium salt to the polyethylene oxide is preferably controlled within a preferred range. If the ratio of the polyethylene oxide is too high, the polyethylene oxide in the matrix will produce more crystalline regions, and the presence of the crystalline regions will inhibit the transmission of lithium ions. On the contrary, if the ratio of the polyethylene oxide is too low, too few alkoxy ether chains will reduce the adsorption capacity for the transmission of lithium ions and reduce the ionic conductivity.
[0014] As a preferred solution, the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide. Preferably, the lithium salt includes a polar organic group, which can improve its dispersibility and dissociation in the organic solid electrolyte.
[0015] The present invention also provides a method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte, which comprises uniformly mixing MCOF-5, polyethylene oxide, lithium salt and solvent, and then performing injection molding, shaping and drying in sequence to obtain the solid electrolyte.
[0016] As a preferred solution, the MCOF-5 is prepared by the following method: polyethylene glycol methyl ether methacrylate and 2-tert-butyloxycarbonylaminoethanethiol undergo free radical addition reaction, and then undergo Boc removal reaction under the action of trifluoroacetic acid to obtain amino-terminated polyethylene glycol, and the amino-terminated polyethylene glycol undergoes coordination reaction with COF-5 to obtain MCOF-5. During the free radical addition reaction, a free radical initiator is used to break the carbon-carbon double bond, and the thiol group combines with the broken double bond to form a carbon-sulfur single bond, thereby introducing an amino group on the double bond of polyethylene glycol methyl ether methacrylate through a free radical addition reaction.
[0017] As a preferred solution, the molar ratio of polyethylene glycol methyl ether methacrylate to 2-tert-butoxycarbonylaminoethanethiol is 1:1.2 to 2. An appropriate excess of 2-tert-butoxycarbonylaminoethanethiol is beneficial to ensure the conversion rate of polyethylene glycol methyl ether methacrylate.
[0018] As a preferred solution, the free radical addition reaction uses azobisisobutyronitrile as a free radical initiator. Preferably, azobisisobutyronitrile is used as a free radical initiator, which can stably generate free radicals at a relatively low temperature, and the reaction is easy to control.
[0019] As a preferred solution, the amount of the free radical initiator is 0.3-1% of the total mass of polyethylene glycol methyl ether methacrylate and 2-tert-butyloxycarbonylaminoethanethiol.
[0020] As a preferred solution, the conditions of the free addition reaction are: temperature of 60-80°C and time of 8-10h. The temperature and time of the free radical addition reaction are extremely important. When the temperature is too low, the carbon-carbon double bond-thiol group cannot effectively undergo free radical addition reaction, and when the temperature is too high, the chemical structure of the monomer will be destroyed to a certain extent, and side reactions such as polymerization will occur; when the time is too short, the reaction is not complete, and when the time is too long, it will cause cross-linking of the polymer. Therefore, reasonable control of the reaction time and temperature is conducive to obtaining the addition product.
[0021] As a preferred solution, the conditions of the Boc removal reaction are: temperature of 40-60°C and time of 6-8h. In the process of Boc removal reaction, trifluoroacetic acid is used as a promoter, and the molar amount of trifluoroacetic acid is 10-20 times the molar amount of polyethylene glycol methyl ether methacrylate (or its free radical addition product). If the amount is too small, the Boc group is not completely removed. In the trifluoroacetic acid environment system, the Boc group reacts to produce carbon dioxide and overflows, and the exposed amino group is conducive to the subsequent coordination reaction.
[0022] As a preferred solution, the conditions of the coordination reaction are: temperature of 20-50°C and time of 6-8h. During the coordination reaction, the amino nitrogen atom in the amino-terminated polyethylene glycol forms a coordination bond with the boron atom in COF-5. The nitrogen atom has two unbonded free electrons in its outermost layer, while the boron atom is sp 2 The outermost layer of the hybrid bond contains an empty P orbital that can accommodate two electrons, so the two can produce a coordinate covalent bond.
[0023] The present invention also provides an application of a flexible segment modified COF-5 composite polymer solid electrolyte for preparing a solid-state lithium-ion battery.
[0024] The preparation process of the solid-state lithium-ion battery involved in the present invention is as follows: assemble the negative electrode shell, negative electrode sheet, solid electrolyte, positive electrode sheet, and positive electrode shell in order. The negative electrode sheet is lithium metal; the preparation steps of the positive electrode sheet are as follows: weigh 0.24g lithium iron phosphate, 0.03g conductive carbon black, 0.03g polyvinylidene fluoride, and 1ml N-methylpyrrolidone and stir them into a uniform slurry, then use a coating machine to evenly scrape it on aluminum foil, dry it at 120°C for 12h under a vacuum of 0.01MPa, and cut it into a positive electrode sheet with a diameter of 12mm using a punching machine.
[0025] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0026] 1) The flexible segment-modified COF-5 composite solid electrolyte of the present invention can effectively improve the transmission rate of metal ions. It contains a large number of ether oxygen atoms that can coordinate with metal lithium ions. In addition, the B, N, and S atoms contained in the material can also dissociate the lithium salt and release more free lithium ions, thereby improving the ionic conductivity of the electrolyte.
[0027] 2) The flexible segment-modified COF-5 composite solid electrolyte of the present invention is used in solid-state lithium-ion batteries, has high ionic conductivity at high temperatures, and improves the coulombic efficiency and cycle life of the battery.
[0028] 3) The preparation method of the flexible segment modified COF-5 composite solid electrolyte provided by the present invention is simple, the raw materials are readily available, the cost is low, and it is suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the infrared spectrum of BOC-NS-PEGMEM in Example 1.
[0030] Figure 2 This is the infrared spectrum of NS-PEGMEM in Example 1.
[0031] Figure 3 This is the infrared spectrum of MCOF-5 in Example 1.
[0032] Figure 4 Graphs showing the ionic conductivity of the MCOF-5 composite solid electrolyte at different temperatures in Examples 3 to 7.
[0033] Figure 5 Graphs showing the ionic conductivity of the solid electrolytes in Examples 3, 5, and 8 at different temperatures. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below through specific embodiments, which should not be construed as limiting the scope of protection of the claims of the present invention.
[0035] The conductivity test was carried out on an SP-200 electrochemical workstation. The prepared MCOF-5 composite solid polymer electrolyte was assembled into a SS / SS (SS, stainless steel electrode sheet) battery. The corresponding formula is:
[0036]
[0037] Where v is the ionic conductivity, L is the electrolyte thickness, S is the contact area between the electrolyte and the stainless steel electrode sheet, and R is the impedance of the electrolyte.
[0038] Example 1 (as a control)
[0039] 1.905 ml of polyethylene glycol methyl ether methacrylate with a molecular weight of 475 mol / g, 1.063 ml of 2-tert-butoxycarbonylaminoethanethiol and 0.09345 g of azobisisobutyronitrile were added into a three-necked flask, followed by the addition of 10 ml of ethyl acetate to completely dissolve it. The mixture was then reacted in a 70°C water bath under argon protection for 8 hours with magnetic stirring. After the free radical polymerization reaction was completed, the mixture was precipitated with an appropriate amount of petroleum ether and dissolved with ethyl acetate. After washing three times, it was placed in a vacuum oven at 80°C for 12 hours to obtain a transparent viscous liquid, recorded as BOC-NS-PEGMEM.
[0040] In a three-necked flask, 3.906 g of BOC-NS-PEGMEM was dissolved in 10 ml of ethyl acetate, and 3.7 ml of trifluoroacetic acid was added to the solution. The mixture was then reacted in a 45°C water bath under argon protection for 8 hours with magnetic stirring. After the de-Boc reaction was completed, the mixture was precipitated with an appropriate amount of petroleum ether and then dissolved with ethyl acetate. After washing three times, it was placed in a vacuum oven at 80°C for 12 hours to obtain a yellow-brown viscous liquid, i.e., a flexible chain segment, recorded as NS-PEGMEM.
[0041] Add 100 mg of COF-5 and 300 mg of NS-PEGMEM to a three-necked flask, then add 10 ml of ethyl acetate to mix them thoroughly, then react in a 45°C water bath under argon protection for 8 hours, and stir with a magnetic bar. After the coordination reaction is completed, the mixture is precipitated with an appropriate amount of petroleum ether, and then dissolved with ethyl acetate. After washing three times, it is placed in a vacuum oven at 80°C for 12 hours to obtain COF-5 modified with flexible segments. After adding more NS-PEGMEM, although the material system has more B and N atoms coordinated, too many flexible molecules gather on the surface of the material, resulting in a non-homogeneous state of the material, affecting the accuracy of subsequent experimental results.
[0042] Example 2
[0043] 1.905 ml of polyethylene glycol methyl ether methacrylate with a molecular weight of 475 mol / g, 1.063 ml of 2-tert-butoxycarbonylaminoethanethiol and 0.09345 g of azobisisobutyronitrile were added into a three-necked flask, followed by the addition of 10 ml of ethyl acetate to completely dissolve it. The mixture was then reacted in a 70°C water bath under argon protection for 8 hours with magnetic stirring. After the free radical polymerization reaction was completed, the mixture was precipitated with an appropriate amount of petroleum ether and dissolved with ethyl acetate. After washing three times, it was placed in a vacuum oven at 80°C for 12 hours to obtain a transparent viscous liquid, recorded as BOC-NS-PEGMEM.
[0044] In a three-necked flask, 3.906 g of BOC-NS-PEGMEM was dissolved in 10 ml of ethyl acetate, and 3.7 ml of trifluoroacetic acid was added to the solution. The mixture was then reacted in a 45°C water bath under argon protection for 8 hours with magnetic stirring. After the de-Boc reaction was completed, the mixture was precipitated with an appropriate amount of petroleum ether and then dissolved with ethyl acetate. After washing three times, it was placed in a vacuum oven at 80°C for 12 hours to obtain a yellow-brown viscous liquid, i.e., a flexible chain segment, recorded as NS-PEGMEM.
[0045] Add 100 mg of COF-5 and 200 mg of NS-PEGMEM into a three-necked flask, then add 10 ml of ethyl acetate and mix them thoroughly. Then react in a 45°C water bath under argon protection for 8 hours with magnetic stirring. After the coordination reaction is completed, the mixture is precipitated with an appropriate amount of petroleum ether and then dissolved with ethyl acetate. After washing three times, it is placed in a vacuum oven at 80°C for 12 hours to obtain COF-5 modified with a flexible segment, recorded as MCOF-5.
[0046] Example 3 (as a control)
[0047] 0.2175 g of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 8 ml of acetonitrile, and ultrasonically dispersed for 30 min to obtain a mixed solution. Then 0.5 g of polyethylene oxide was added, stirred at room temperature for 12 h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6 h, and then vacuum dried at 60 ° C for 12 h to obtain a composite polymer electrolyte, which was recorded as PEO (0%). At room temperature, the ionic conductivity was 4.03×10 -5 S / cm.
[0048] Example 4
[0049] 0.2175 g of lithium bis(trifluoromethanesulfonyl)imide and 0.015 g of MCOF-5 (prepared in Example 2) were dissolved in 8 ml of acetonitrile, and ultrasonically dispersed for 30 min to obtain a mixed solution. Then, 0.5 g of polyethylene oxide was added, stirred at room temperature for 12 h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6 h, and then vacuum dried at 60°C for 12 h to obtain a composite polymer electrolyte, which was recorded as PEO / MCOF-5 (3%). At room temperature, the ionic conductivity was 5.50×10 -5 S / cm.
[0050] Example 5
[0051] 0.2175 g of lithium bis(trifluoromethanesulfonyl)imide and 0.025 g of MCOF-5 (prepared in Example 2) were dissolved in 8 ml of acetonitrile, and ultrasonically dispersed for 30 min to obtain a mixed solution. Then, 0.5 g of polyethylene oxide was added, stirred at room temperature for 12 h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6 h, and then vacuum dried at 60°C for 12 h to obtain a composite polymer electrolyte, which was recorded as PEO / MCOF-5 (5%). At room temperature, the ionic conductivity was 8.41×10 -5 S / cm.
[0052] Example 6
[0053] 0.2175 g of lithium bis(trifluoromethanesulfonyl)imide and 0.035 g of MCOF-5 (prepared in Example 2) were dissolved in 8 ml of acetonitrile, and ultrasonically dispersed for 30 min to obtain a mixed solution. Then, 0.5 g of polyethylene oxide was added, stirred at room temperature for 12 h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6 h, and then vacuum dried at 60°C for 12 h to obtain a composite polymer electrolyte, which was recorded as PEO / MCOF-5 (7%). At room temperature, the ionic conductivity was 4.85×10 -5 S / cm.
[0054] Example 7
[0055] 0.2175 g of lithium bis(trifluoromethanesulfonyl)imide and 0.045 g of MCOF-5 (prepared in Example 2) were dissolved in 8 ml of acetonitrile, and ultrasonically dispersed for 30 min to obtain a mixed solution. Then, 0.5 g of polyethylene oxide was added, stirred at room temperature for 12 h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6 h, and then vacuum dried at 60°C for 12 h to obtain a composite polymer electrolyte, which was recorded as PEO / MCOF-5 (9%). At room temperature, the ionic conductivity was 4.61×10 -5 S / cm.
[0056] Example 8 (as a control)
[0057] 0.2175g of lithium bis(trifluoromethanesulfonyl)imide and 0.025g of COF-5 were dissolved in 8ml of acetonitrile, and ultrasonically dispersed for 30min to obtain a mixed solution. Then 0.5g of polyethylene oxide was added, stirred at room temperature for 12h, and then poured into a polytetrafluoroethylene mold. The mixture was first dried at room temperature for 6h, and then vacuum dried at 60℃ for 12h to obtain a composite polymer electrolyte, which was recorded as PEO / COF-5 (5%). At room temperature, the ionic conductivity was 4.06×10 -5 S / cm.
Claims
1. A flexible segment modified COF-5 composite polymer solid electrolyte, characterized in that: It contains the following components: MCOF-5, polyethylene oxide and lithium salt; The MCOF-5 is obtained by coordination between polyethylene glycol modified with terminal amino groups and COF-5; The mass ratio of COF-5 to the amino-terminated polyethylene glycol in the MCOF-5 is 1:1-2; The mass ratio of MCOF-5 to polyethylene oxide is 3-9:100; The ratio of the lithium salt to the polyethylene oxide is measured by a molar ratio of lithium ions in the lithium salt to oxygen atoms in the polyethylene oxide of 1:15-20; The number average molecular weight Mn of the amino-terminated polyethylene glycol is 400-800 g / mol.
2. The flexible segment modified COF-5 composite polymer solid electrolyte according to claim 1, characterized in that: The lithium salt includes lithium bis(trifluoromethanesulfonyl)imide.
3. The method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte according to claim 1 or 2, characterized in that: The MCOF-5, polyethylene oxide, lithium salt and solvent are uniformly mixed, and then injection molding, shaping and drying are performed in sequence to obtain the product.
4. The method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte according to claim 3, characterized in that: The MCOF-5 is prepared by the following method: polyethylene glycol methyl ether methacrylate and 2-tert-butyloxycarbonylaminoethanethiol undergo free radical addition reaction, and then undergo Boc removal reaction under the action of trifluoroacetic acid to obtain amino-terminated polyethylene glycol, and the amino-terminated polyethylene glycol undergoes coordination reaction with COF-5 to obtain MCOF-5.
5. The method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte according to claim 4, characterized in that: The molar ratio of the polyethylene glycol methyl ether methacrylate to 2-tert-butyloxycarbonylaminoethanethiol is 1:1.2-2.
6. The method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte according to claim 4, characterized in that: The free radical addition reaction uses azobisisobutyronitrile as a free radical initiator; The amount of the free radical initiator is 0.3-1% of the total mass of polyethylene glycol methyl ether methacrylate and 2-tert-butyloxycarbonylaminoethanethiol; The conditions of the free radical addition reaction are: temperature of 60-80°C and time of 8-10h; The conditions of the de-Boc reaction are: temperature of 40-60° C. and time of 6-8 h.
7. The method for preparing a flexible segment modified COF-5 composite polymer solid electrolyte according to claim 4, characterized in that: The conditions of the coordination reaction are: temperature of 20-50° C. and time of 6-8 h.
8. An application of a flexible segment modified COF-5 composite polymer solid electrolyte, characterized in that: Used to prepare solid-state lithium-ion batteries.
Citation Information
Patent Citations
Solid polymer electrolyte added with graphene quantum dots and preparation method of solid polymer electrolyte
CN106848394A